Mild traumatic brain injury : a science and engineering perspective - Mentzer, Mark A. (Boca Raton : CRC Press, 2021)
"Mild traumatic brain injury, also known as chronic traumatic encephalopathy, presents a crisis in contact sports, the military, and elsewhere. This book reviews current understanding of mTBI, methods of diagnosis, treatment, policy concerns, and emerging technologies. This book details the neurophysiology, epidemiology of brain injuries by presenting disease models and descriptions of nucleating events"--
Clinical Sequelae and Functional Outcomes -- Diagnosing mTBI -- Instrumentation for Assessing mTBI events -- mTBI in the Military and Contact Sports -- Therapeutic Strategies and Future Research.
OCLC-licensed vendor bibliographic record.
Keywords: Chronic traumatic encephalopathy; Brain -- Concussion